Gibbs measures on subshifts - Kimura, Bruno Hideki Fukushima (2015)
We study the properties of Gibbs measures for functions with d-summable variation defined on a subshift X. Based on Meyerovitch\'s work from 2013, we prove that if X is a subshift of finite type (SFT), then any equilibrium measure is also a Gibbs measure. Although the definition provided by Meyerovitch does not make any mention to conditional expectations, we show that in the case where X is a SFT it is possible to characterize these measures in terms of more familiar notions presented in the literature.